PENGARUH SELEBRITI ENDORSEMENT PADA PERIKLANAN TERHADAP NIAT PEMBELIAN MAHASISWA UNSYIAH (Studi Kasus Pada Pengguna Belanja Online) - Mutia Rahmi, Srinita (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2018)
This study intend to examine the Effect of Celebrity Endorsement on Advertising the Purchasing Intention of Unsyiah Student  in Banda Aceh, and see the difference in the influence of two variables on purchase intention. The sampling method in this study is purposive sampling, the sampling based on certain criteria. Data analysis methods are used to see the influence of celebrity endorsement on advertising on purchase intentions at FEB Unsyiah is to use the Path Analysis method. The results showed that Celebrity endorsement partially significant effect on advertising . Endorsement celebrities partially have a significant effect on student purchase intentions. Advertising partially has a significant effect on student purchase intentions. Endorsement celebrities, and advertising together have a significant effect on student.